Visna virus as an in vitro model for human immunodeficiency virus and inhibition by ribavirin, phosphonoformate, and 2',3'-dideoxynucleosides. - Frank, K B (1987)
Inhibition of visna virus replication in vitro by several compounds previously reported to inhibit replication of human immunodeficiency virus (HIV) was examined. Ribavirin concentrations as high as 1 mM reduced virus production by less than 50% relative to controls. The concentration of phosphonoformate reducing virus replication by 50% was 80 microM. 2',3'-Dideoxynucleosides were potent inhibitors of visna virus replication. The 50% inhibitory concentrations for dideoxyguanosine, dideoxyadenosine, and dideoxycytidine were 0.1, 0.2, and 0.3 microM, respectively. In contrast, weak inhibition was produced by 100 microM dideoxythymidine. These results are consistent with the reported susceptibility of HIV replication to inhibition by these compounds in vitro. The interaction of visna virus reverse transcriptase with several inhibitors was also examined. Reverse transcriptase was inhibited by phosphonoformate, ribavirin 5'-triphosphate, ddATP, ddCTP, ddGTP, and ddTTP. The last four compounds inhibited incorporation of homologous 2'-deoxynucleoside 5'-triphosphates into polynucleotides by a competitive mechanism. In view of the biological similarities between visna virus and HIV and the similar in vitro susceptibility of visna virus replication to known inhibitors of HIV, visna virus may provide a good model for studying the inhibition of HIV replication in vitro. Because visna virus is not pathogenic to humans, this model may facilitate the identification of compounds for further investigation into the treatment of HIV-induced disease.